085. Survival Time of Anaplastic Thyroid Cancer with Various of Therapeutic Modalities - Wibawa, I Gede Arya Eka; Adiputra, Putu Anda Tusta; Sudarsa, I Wayan (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p085, 2024)
Background : Anaplastic carcinoma of the thyroid (ATC) is the most aggressive thyroid gland malignancy. Therapies modalities were controversial due to its poor survival prognosis. The survival data after various therapeutic modalities for ATC is still limited. Methods: This study is a retrospective cohort study by taking data from the Cancer Registry in Bali, Denpasar, Indonesia. All patients with anaplastic thyroid cancer who visited Sanglah Hospital in the range 2018 to 2020 were included in this study. Data regarding duration of survival, received treatment modalities, tumor size from radiological data, and laboratories were analyzed with SPSS 25.0. Results : This study included 10 subjects with ATC, mostly male with a mean age of 60.7 years old. The mean survival was 74.8 days with a median survival of 74.5 days. Of the ten patients, 2 patients died without getting any therapy, both surgical and medical therapy. In this study, there was a significant difference in duration of survival between therapeutic modalities. There was no influence of tumor volume factors, gap from initial presentation to therapeutic modality, nodes involved, blood gas analysis at the initial presentation, NLR, PLR, TSH, and FT4 for the survival time of anaplastic thyroid cancer. Conclusion : There is a significant difference in duration of survival between therapeutic modalities for anaplastic ca thyroid. Even so, isthmectomy, tracheostomy, and chemotherapy therapy, only provide an extension of survival time for an average of 40 days.